The Effect Of Earnings Per Share (EPS), Return On Assets (ROA), And Debt To Equity Ratio (DER) On Stock Prices With Dividend Policy As A Moderating Variable - Nengsi, Surya; Sofyan, Syaakir; Pakkawaru, Irham (Journal of Contemporary Economics and Business Management, 2026)
This study aims to analyze the effect of Earnings Per Share (EPS), Return on Assets (ROA), and Debt to Equity Ratio (DER) on stock prices, and examine the role of dividend policy as a moderating variable in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. This study uses a quantitative approach with an explanatory research design. The population consisted of 270 companies, with a sample of 47 companies selected through a purposive sampling method, resulting in 141 observations. Data analysis used panel data regression with the Fixed Effect Model (FEM) approach and Moderated Regression Analysis (MRA) using EViews 12. The results showed that EPS had a positive and significant effect on stock prices, while ROA and DER each had a negative and significant effect. Simultaneously, all variables had a significant effect with an R² value of 97.46%. However, dividend policy was not proven to moderate the effect of EPS, ROA, or DER on stock prices. This finding indicates that investors respond more directly to a company’s fundamental information without considering its interaction with dividend policy.